The Analysis Study of Yoga and Cognitive in Older Adults: A Systematic Review and Metaanalysis - Pretika Prameswari; Yudhi Hajianto Nugroho; Mutia Juliana (The Indonesian Journal of General Medicine, 2025)
Background: Yoga practices, focusing on mindfulness and meditation, have been found to positively impact cognitive function in older adults. These practices improve physical health, balance, flexibility, and cardiovascular function, while also promoting brain plasticity, neurogenesis, and stress-induced damage. The social aspect of yoga classes may also reduce isolation, thereby reducing cognitive decline. This study aims to provide a comprehensive analysis of existing research on the effects of yoga on cognitive function in older adults. Method: This systematic review was conducted in accordance with the PRISMA 2020 guidelines, focusing solely on full-text articles published in English between 2014 and 2024. To ensure the inclusion of high-quality, peer-reviewed sources, editorial pieces and review articles lacking a DOI were excluded. A comprehensive literature search was carried out across several reputable databases, including ScienceDirect, SpringerLink, PubMed, and SagePub, to identify pertinent studies that met the inclusion criteria. Result: The initial database search yielded over 1,000 relevant publications on the topic. Following a rigorous three-stage screening process, eight studies met the predefined inclusion criteria and were selected for in-depth analysis. Each study underwent a comprehensive critical evaluation, enabling a thorough examination of the relationship between psoriasis and hypertension. This systematic approach ensured that the analysis was grounded in high-quality evidence, closely aligned with the study's objectives, and capable of providing meaningful insights into this complex association. Conclusion: Yoga has been found to have beneficial effects on cognitive function in older adults, although methodological limitations and inconsistencies in intervention design need further investigation. Further research is needed to determine the true efficacy of yoga in promoting cognitive health among this age group.